Reducing packaging waste to promote a circular economy of Phuket Province - สิริพันธ์พงศ์, ปิ่นรัตน์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
Phuket Province faces significant environmental problems related to waste, impacting its tourism image. Approximately 1,000-1,200 tons of waste are generated daily, with about 700 tons incinerated per day, leaving approximately 500 tons remaining. This academic article has objective to suggest ways to reduce plastic packaging waste, offering alternatives for a circular economy. The approach involves reducing the volume of waste before incineration, such as using bioplastics, label-free bottles, reducing packaging size, using edible packaging, and producing packaging-free products. Waste should then be separated into three parts: Firstly, combustible waste (energy waste) should be incinerated. Excess plastic packaging beyond the incineration capacity should be recycled to add value through upcycling, such as crushing plastic pellets, using plastic fibers from clothing, melting and molding plastic waste into construction materials like artificial wood, bricks, and house walls, or compressing it into RDF (Refuse Derived Fuel) fuel, and using pyrolysis to refine crude oil. Secondly, organic waste, comprising half of all waste and contributing to air pollution, should be used as animal feed if in good condition, or composted to produce biogas or dried for fertilizer if unusable. Thirdly, waste that should not be incinerated includes metals, which should be melted and reused, and glass bottles, which should be crushed into powder for sand production. The proposed construction materials or land reclamation projects on Phuket Island will, as seen in this article, positively impact Phuket's waste problem. They promote alternatives for reducing packaging waste, add value, and foster a circular economy in the province. Furthermore, they align with the Sustainable Development Goals (SDGs) 14, which focuses on conserving and sustainably utilizing the oceans, seas, and marine resources for sustainable development. However, a high level of understanding and participation from all stakeholders is required to ensure Phuket remains a primary tourist destination and continues to generate revenue for Thailand.